Fucoidan-Mediated Anisotropic Calcium Carbonate Nanorods of pH-Responsive Drug Release for Antitumor Therapy - Wang, Pei; Tong, Fei; Luo, Jun; Li, Zhihua; Wei, Junchao; Liu, Yuangang (Frontiers in Bioengineering and Biotechnology, 2022)
The shape of nanoparticles can determine their physical properties, and then greatly impact physiological reactions on cells or tissues at treatment. Traditionally spherical nanoparticles are more widely applied in biomedicine, but not necessarily the best. The superiority of anisotropic nanoparticles has been come to realize in recent years. The synthesis of the distinct-shape metal/metal oxides nanoparticles is easily controlled. However, their biotoxicity is still up for debate. Hence, we designed CaCO3 nanorods for drug delivery prepared at mild condition by polysaccharide-regulated biomineralization in the presence of fucoidan with sulfate groups. CaCO3 nanorods with pH-sensitivity loaded anti-tumor drug mitoxantrone hydrochloride (MTO) showed excellent anti-tumor efficacy for HeLa cells and MCF-7 cells in vitro. We believe that anisotropic nanoparticles will bring forth an emblematic shift in nanotechnology for application in biomedicine.